STUDENT CHARACTER EDUCATION BASED ON KINSHIP AND SOLIDARITY VALUES OF HOMBO BATU TO REDUCE CONFLICTS IN SCHOOLS - Darmawan Harefa (LPPM Universitas Nias Raya, 2025)
This study aims to explore the integration of kinship and solidarity values derived from the Hombo Batu tradition into student character education to reduce conflicts in a senior high school in South Nias, Indonesia. Hombo Batu, a culturally significant local practice, emphasizes mutual cooperation, collective responsibility, and respect for peers and elders. Despite its potential, the values of Hombo Batu are rarely incorporated into formal educational settings, leaving students prone to interpersonal conflicts and diminished social cohesion. The study employed a mixed-methods approach, combining surveys, observations, and interviews with students and teachers to assess changes in attitudes, behavior, and peer interactions following a series of value-based educational interventions. The intervention included peer-group activities, reflective discussions, and culturally framed conflict-resolution exercises. Results indicate that students internalized kinship and solidarity values, demonstrated increased empathy, and engaged in cooperative behaviors that significantly reduced instances of conflict. Furthermore, institutional strategies such as monthly “Solidarity Sessions” and student “Kinship Ambassadors” helped embed these values into the school’s daily culture. The findings suggest that character education rooted in local wisdom not only enhances students’ ethical development but also fosters a harmonious learning environment. This culturally grounded approach provides a model that can be adapted in other schools seeking to strengthen social cohesion and reduce conflict through contextually relevant character education.